1983
DOI: 10.1002/ajmg.1320140114
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of 16p from insertion of 16p into 16q with subsequent duplication due to crossing over within the inserted segment

Abstract: Two members of a large family had a similar multiple congenital anomalies mental retardation (MCA/MR) syndrome and an identical aberration of chromosome 16. Their mothers, who are first cousins, had a different abnormality of one chromosome 16, which appeared to be an acrocentric. We interpret these findings as an insertion of a segment of 16p into 16q. following a three-break rearrangement and meiotic crossing over. The two abnormal children have a duplication of 16p11 leads to p13. The clinical manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…Two patients with a duplication of chromosome region 16p11 ! 16p13 due to meiotic crossing-over involving a familial intra-chromosomal insertion translocation (16)(p13p11q11) are reported by Cohen et al [1983]. Some of the (non-specific) clinical features present in patients with complete trisomy 16p were also present in the latter patients: low birth weight, reduced OFC, apparently low-set ears, and psychomotor retardation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Two patients with a duplication of chromosome region 16p11 ! 16p13 due to meiotic crossing-over involving a familial intra-chromosomal insertion translocation (16)(p13p11q11) are reported by Cohen et al [1983]. Some of the (non-specific) clinical features present in patients with complete trisomy 16p were also present in the latter patients: low birth weight, reduced OFC, apparently low-set ears, and psychomotor retardation.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, a rounded face with prominent glabella, hypertelorism, narrow palpebral fissures, depressed nasal bridge, anteverted nostrils, a thin upper lip and low set ears are reported. Partial trisomy of 16p is reported in five patients [Cohen et al, 1983;Hebebrand et al, 1994;Carrasco Juan et al, 1997;Kokalj-Vokac et al, 2000] and triplication of chromosome region 16p13.1 ! 16p13.2 appears to lead to the specific trisomy 16p syndrome.…”
Section: Introductionmentioning
confidence: 96%
“…From centromere to telomere, these include first, the common microdeletions/duplications of B600 kb in 16p11.2 associated with neurocognitive difficulties and obesity; [2][3][4] second, the microscopically visible duplications of 8-9 Mb from 16p11.2 to 16p12.1/2 associated with developmental delay and autism [5][6][7][8][9][10][11] and the reciprocal microdeletions associated with developmental delay, intellectual disability and subtle dysmorphic features; 12,13 within these are, third, the distal (formerly atypical) microdeletions of B220 kb in 16p11.2 associated with a phenotype that includes developmental delay or obesity but extends into the normal range [14][15][16] and, fourth, the microdeletions/duplications of B520 kb in 16p12.1 associated with developmental delay. 1, 17 Here, we report two new patients with cytogenetically visible duplications of 16p11.2-16p12.2 analysed using oligonucleotide array comparative genomic hybridisation (oaCGH) and compared with 10 previous postnatal patients.…”
Section: Introductionmentioning
confidence: 99%
“…1, 17 Here, we report two new patients with cytogenetically visible duplications of 16p11.2-16p12.2 analysed using oligonucleotide array comparative genomic hybridisation (oaCGH) and compared with 10 previous postnatal patients. [5][6][7][8][9][10][11] CNV is common with over 66 000 examples recorded in the Database of Genomic Variants (DGV) and an estimated 1% of the human population having a CNV 41 Mb. 1 When copy number is high enough, rare CNVs of 8p23.1, 9p12, 9qh/q12, 9q13, 15q11.2 and 16p11.2 become visible in the light microscope and have been described as euchromatic variants.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, 9 cases of complete [Magnelli, 1976;Yunis et al, 1977;Roberts and Duckett, 1978;Dallapiccola et al, 1979;Leschot et al, 1979;Llamas et al, 1981;Jalal et al, 1989;Léonard et al, 1992;Schinzel, 2001] and 32 cases of partial and/or mosaic [Stern and Murch, 1975;Rada and Sandlin, 1982;Cohen et al, 1983;McMorrow et al, 1984;Hunter et al, 1985;Mori et al, 1987;Bofinger et al, 1991;O'Connor and Higgins, 1992;Brandt et al, 1994;Hebebrand et al, 1994;Preis et al, 1996;Carrasco Juan et al, 1997;Schinzel et al, 1997;Movahhedian et al, 1998;Chen et al, 1999;Kokalj-Vokac et al, 2000;Engelen et al, 2002;Tschernigg et al, 2002;Kupchik et al, 2005;de Ravel et al, 2005;Sommer et al, 2006] Stern et al [1975]; Mori et al [1987]; Chen et al [1999], and Kupchik et al [2005] each reported a child with a duplication of 16p combined with other duplications or deletions; these are not included in this review. Golden et al [1981] published a propositus having an ''extra genetic material'' present on the short arm of chromosome 16 that was, however, not identified.…”
Section: Discussionmentioning
confidence: 98%